Effect of nitrogen concentration on the yield and biochemical characteristics of exopolysaccharide of Porphyridium purpureum - Li, Qianmei; Xu, Jin; Chen, Yi; Xiang, Wenzhou; Wu, Houbo; Gan, Songyong; Li, Aifen; Li, Tao (Frontiers in Marine Science, 2025)
Exopolysaccharides (EPS) of Porphyridium purpureum have attracted much attention in biotechnology due to their unique physicochemical properties and bioactivities. Nitrogen is a critical environmental factor affecting microalgal metabolism, but its effect on the structural characteristics of EPS is not widely reported. This study aimed to investigate the effects of nitrogen concentrations on EPS production and the structural properties of P. purpureum by determining the yield, substituents proportions and molecular weight of EPS. The results showed that nitrogen concentrations of 9.0 mM and 18.0 mM optimized cell division, while photosynthetic efficiency decreased as nitrogen concentration decreased. Nitrogen concentration was positively correlated with total EPS yield, with the highest yield (663.5 mg L-1) observed at 54.0 mM. Furthermore, the proportions of carbohydrates, proteins and uronic acid in EPS increased with rising nitrogen concentrations. The monosaccharide composition (xylose, glucose and galactose) and the molecular weight of EPS (ranging from 6.6 to 8.3 × 106 Da) were also influenced by nitrogen concentration. In conclusion, nitrogen concentration significantly influences the synthesis and biochemical characteristics of EPS in P. purpureum, offering new insights for structural modifications and biotechnological applications of EPS.